Inflammatory Risk Factors for Chronic Subdural Hematoma in a Nationwide Cohort - Jensen TSR; Thiesson EM; Fugleholm K; Wohlfahrt J; Munch TN (Dove Medical Press, 2024)
Thorbjørn Søren Rønn Jensen,1 Emilia Myrup Thiesson,2 Kåre Fugleholm,1 Jan Wohlfahrt,2,3 Tina Nørgaard Munch1,2 1Department of Neurosurgery, Copenhagen University Hospital, Copenhagen, DK-2100, Denmark; 2Department of Epidemiology Research, Statens Serum Institute, Copenhagen, DK-2300, Denmark; 3Danish Cancer Society Research Center, Copenhagen, DK-2100, DenmarkCorrespondence: Thorbjørn Søren Rønn Jensen, Email tjens07@gmail.comBackground: The discovery of biomarkers in chronic subdural haematomas (CSDH) suggests that inflammation is part of CSDH pathophysiology. It is unknown whether inflammation reflects an independent CSDH driver or haematoma degeneration. This knowledge holds a potential target for anti-inflammatory treatment in patients at risk of CSDH. This study investigated the association of pro- and anti-inflammatory factors with CSDH development.Methods: This cohort study included all individuals in Denmark over 50 years between 2007- 2018. The outcome was first-time CSDH surgery. Hazard ratios (HR) according to potential risk factors were estimated using Cox regression, with age as underlying time scale.Results: Among the 2,391,853 individuals, head trauma was registered in 427,612 individuals (17%), and among these, only 812 were operated for CSDH (0.18%). Among individuals without registered head trauma, the pro-inflammatory conditions of alcohol addiction, diabetes, anti-hypertensive treatment, and chronic hepatic disease were significantly associated with CSDH among individuals (50- 74 years). The use of glucocorticoids displayed a decreased risk in cohort members aged 75 and older. Non-steroid anti-inflammatory drugs and statins appeared to be risk factors for CSDH in individuals between the ages of 50- 64 and 65- 74.Conclusion: Although head trauma was a risk factor for CSDH, the absolute risk was low (0.18%), which does not support preventive measures after emergency room contacts for head trauma. Interestingly, pro-and anti-inflammatory factors were significantly associated with CSDH in patients without registered head trauma, and the pronounced age-dependency of the associations suggests that the pathophysiological mechanisms vary with age.Keywords: head trauma, inflammation, trauma, anti-inflammatory treatment, risk factors